Environmental Governance for Sustainable Tourism in Socio-Ecological Systems: A Systematic Literature Review - Sitti Mutiah Rahman; Fitryane Lihawa; Dewi Wahyuni K. Baderan (Westscience Press, 2025)
Tourism destinations are increasingly understood as socio-ecological systems (SES) where ecological dynamics, livelihoods, and institutions interact through feedback loops. This systematic literature review synthesises evidence on how environmental governance shapes sustainable tourism trajectories in tourism-dependent SES and highlights gaps for future research. Peer-reviewed journal articles (2000–2025) were identified through structured searches in major databases and complementary searches, then screened using predefined eligibility criteria and appraised for methodological quality using a mixed-methods-appropriate tool [9]. Forty-six studies were retained for narrative thematic synthesis. The evidence indicates that governance in tourism SES is commonly hybrid—combining hierarchical regulation, market mechanisms, and community participation—and is implemented through instrument mixes such as zoning, permitting, environmental standards, economic incentives, and stakeholder forums. Across protected areas, coastal zones, rural landscapes, and urban destinations, collaborative arrangements (e.g., co-management and community-based models) are more frequently linked with biodiversity protection, improved habitat condition, and livelihood diversification than fragmented or investor-dominated regimes [1], [2], [3]. However, outcomes vary substantially and are mediated by enforcement capacity, institutional coherence, perceived legitimacy, and distributional fairness [4], [5]. The review also shows an expanding methodological toolkit (remote sensing, composite indices, modelling), but persistent gaps in longitudinal designs and in indicators that capture equity, resilience, and linked human–environment risks [6], [7]. Overall, sustainable tourism in SES requires adaptive, cross-scale, and equity-oriented governance that can learn from monitoring and address power asymmetries.